Ten “Rs” of social reaction: using social media to analyse the “post-event” impacts of the murder of Lee Rigby - Innes, Martin (Terrorism and political violence, 2018)
This article provides a case study analysis of social reactions to the murder of Fusilier Lee Rigby in 2013. Informed by empirical data collected by systematic monitoring of social media platforms, the analysis identifies a number of online behaviours with offline effects—labeled the ten “Rs”—that collectively constitute the process of social reaction to the crime. These are defined as: reporting; requesting; responding; recruiting; “risking”; retaliating; rumouring; remembering; reheating; and “resiliencing”. It is argued that the ability to observe these behaviours through the application of qualitative social media analysis has considerable potential. Conceptually, the analysis provides new insight into the complex and chaotic processes of sense-making and meaning attribution that arise in the aftermath of terrorist attacks. It illuminates how patterns of social reaction on social media are nuanced and complicated, with different segments of the public interpreting the same developments very differently. In addition, the findings and the conceptual framework outlined have implications for policy and practice development in terms of establishing a more effective and evidence-based approach to the consequence management of “post-event” conflict dynamics and social reactions.